Combining Dexmedetomidine and Airway Blocks for Awake Airway Access: Insights from Three Clinical Cases - Dr. Raju Shakya; Dr. Sunny Aggarwal; Dr. Mukul Garg (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Airway management in patients with anticipated difficult airway anatomy poses significant challenges to anaesthesiologists. Techniques such as conscious sedation with dexmedetomidine and regional airway blocks offer an alternative to general anesthesia, providing adequate sedation while preserving spontaneous ventilation and airway reflexes. This case series presents three patients with challenging clinical case scenarios and airway anatomy managed successfully using combination of conscious sedation and regional airway blocks.